COVID-19 vaccination in patients with cancer: Opportunities and challenges - Al-qaim, Zahraa Haleem; Owadh, Hasanain Kamil Hasan; Ali, Sarah A.; Hussein, Alaa S.; Ameen, Thamer Ramadhan; Kolemen, Ayshan; Washi, Ghassan A.; Jalil, Abduladheem Turki (Frontiers in Oncology, 2022)
The rapid spread of the SARS-Cov-2 virus, the increase in the number of patients with severe COVID-19, and the high mortality rate created the basis for the production of safe and effective vaccines. Studies have confirmed the increased risk of severe Covid-19 disease and mortality in cancer patients. It is logical that cancer patients should be the first to receive the primary vaccination and the booster vaccine for Covid-19. Since studies related to cancer patients and the effectiveness of existing Covid-19 vaccines have not been widely conducted, there are significant uncertainties about the effectiveness of the vaccine and the level of humoral and cellular immune responses in these patients. As a result, the possible risks and side effects of existing vaccines are not clear for patients with different cancers who are undergoing special treatments. In this study, we will discuss the effectiveness and safety of existing vaccines on cancer patients. In addition, we highlight factors that could affect the effectiveness of vaccines in these patients and finally discuss opportunities and challenges related to vaccination in cancer patients.